TELEMETERING OF SHIP LOAD WITH SMARTPHONE BASED ON NODEMCU ESP8266 (International Journal of Psychosocial Rehabilitation, 2020)
At the Dockyard there is no device that can measure ship loads. The purpose of this study is to determine and measure ship loads. This study uses protoype of shipbuilding with ultrasonic sensors to determine the rise in water when there is a ship to be measured.The load sensor readings will be processed using NodeMcu which is displayed on the Blynk application which can be accessed on a smartphone in the form of water level.